Application of the Principle of Legal Certainty in the Execution of an Arbitral Award in Indonesia - Vivi Vivi; L.Alfies Sihombing; Yeni Nuraeni (Publikasi Indonesia, 2024)
In principle, the legal system regulates the life of a community so that conflicts do not occur, although often these conflicts cannot be avoided, a principle of legal certainty is needed in resolving disputes through arbitration and how the execution of an arbitral award in Indonesia can be applied or implemented. The legal system has an important role to play in resolving these conflicts. The legal system in the judicial world has a major influence in the application of law, especially for judges in examining and deciding a case. Judges in deciding a case will definitely pay great attention to the legal system in their jurisdiction. In addition, the Panel of Judges uses the decisions of other judges who decide cases whose substance in principle has similarities to be used as a reference and consideration in deciding a case.